Efek Pemberian Madu Terhadap Nyeri Pasca Tonsilektomi: Tinjauan Sistematis - Rafika Nurul Aini (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Tonsillectomy is one of the most common ENT surgeries. Immediate complications following tonsillectomy include pain, bleeding, pulmonary edema, foreign body aspiration, and fever. Honey accelerates and facilitates wound healing, and its antimicrobial and anti-inflammatory properties reduce stomach ulcers, including sore throats caused by tonsillectomy/adenotonsillectomy. Study systematic review of randomized controlled trials (RCTs) describes the effect of post-tonsillectomy pain relief with honey. Scopus, science direct, springer link and web of science collaborative library database searches were carried out without limitation on the year of publication. The end date of the search was 23 April 2022. Inclusion criteria were RCTs related to postoperative tonsillectomy pain relief associated with complementary honey treatment. Postoperative pain was measured by VAS, amount of pain medication taken, percentage of patients taking pain medication, time to pain relief, and pain when swallowing or radiating to the ear. Pain by VAS: Honey significantly improved postoperative pain compared to controls from day 1 to 7 (P = 0.05 to <0.0001). Giving honey is an alternative action, easy to obtain, classified in complementary medicine, and can be used by nurses in managing pain in patients and reducing pain levels. Giving honey is a non-pharmacological therapy that is effective in reducing pain levels in post-tonsilectomy patients.